Pemberdayaan Ekonomi Berbasis Potensi Kemaritiman Bagi Masyarakat Dan Nelayan Di Kelurahan Pohe Kota Gorontalo - Wiwin Rewini Kunusa; Julhim S Tangio; Sitty Salsabilla Ishak; Indah Rahayu Sanusi; Siti Nur Hikma H. Hasbula; Azrila Natania Korompot (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
Pohe Village, located in Hulonthalangi District, Gorontalo City, is a coastal area with significant maritime potential that serves as the primary source of livelihood for local communities, particularly fishermen. However, the sustainability of coastal livelihoods is challenged by economic, environmental, climate, and social issues. This study aimed to identify the current conditions of the coastal community and explore strategies for maritime-based economic empowerment to support sustainable development. A descriptive quantitative approach supported by qualitative data was employed through questionnaires, interviews, and seawater quality assessments conducted at four sampling locations. A total of 30 respondents were selected using incidental sampling techniques. The findings revealed that the community's economic condition remains vulnerable due to fluctuating fish prices, seasonal changes, and declining fish catches. Environmental assessment indicated that coastal water quality is generally good, characterized by clear and odorless water, neutral to slightly alkaline pH levels, and adequate dissolved oxygen concentrations. Nevertheless, coastal waste accumulation remains a major environmental concern. The community has also begun to experience the impacts of climate change, including unpredictable weather patterns, increased wave intensity, and flooding that transports waste and sediment into residential areas. In contrast, social conditions were relatively favorable, supported by access to healthcare services, basic facilities, and government assistance programs. Therefore, coastal economic empowerment should be implemented through an integrated approach involving the strengthening of fishermen’s capacities, sustainable coastal environmental management, and supportive government policies. Such efforts are expected to enhance community welfare while ensuring the sustainability of maritime resources and coastal ecosystem.